2019
DOI: 10.3389/fimmu.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Signaling Pathways Linked to sIgAD Reveals Impaired IL-21 Driven STAT3 B-Cell Activation

Abstract: Objectives: It has recently been shown that individuals with selective IgA deficiency (sIgAD) have defective B cell responses both to T cell dependent and independent mimicking stimulations. The complex intracellular signaling pathways from different stimuli leading to IgA isotype switching have not been fully elucidated. Thus, the main objective of this study was to delineate these pathways and their potential role in the immunopathology linked to sIgAD.Materials and Methods: PBMCs from 10 individuals with sI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…We recently observed significantly decreased of the transitional B cells AT [ 29 ]. In contrast to previous studies that showed decreased transitional B cells [ 8 , 28 , 40 ], adult patients indicated slightly increased transitional B cells. Moreover, Lemarquis et al showed a decrease in the functional activity of transitional B cells based on IL-10 production and CpG stimulation [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We recently observed significantly decreased of the transitional B cells AT [ 29 ]. In contrast to previous studies that showed decreased transitional B cells [ 8 , 28 , 40 ], adult patients indicated slightly increased transitional B cells. Moreover, Lemarquis et al showed a decrease in the functional activity of transitional B cells based on IL-10 production and CpG stimulation [ 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have demonstrated B cell and T cell abnormalities in some groups of SIgAD patients [ 3 , 4 ]. Regarding B cell subsets, a decrease in the number of switched memory B cells, IgA plasma cells and transitional IL-10 + regulatory B cells of SIgAD patients has been reported [ 5 8 ]. On the other hand, defect in some T cell subsets of SIgAD cases have been reported that is linked to insufficient IgA-producing B cells [ 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%